Bacterial Contamination on Meatballs Sold in Traditional Markets P.D. Surya Market in East Surabaya Region Causes a Decline in People's Income - Alfiyatus Sholichah; Ratna Yulistiani; Ulya Sarofa; Dadik Raharjo (Budapest International Research and Critics University, 2022)
Coliform, Escherichia coli and Salmonella sp. are bacterial pathogen that causes foodborne disease which often contaminates food that is harmful to human health. The sale of meatballs without packaging accompanied by poor hygiene and environmental sanitation conditions has a high potential for contamination by Coliform, Escherichia coli and Salmonella sp. The purpose of this study was to identify the contamination of Coliform, Escherichia coli and Salmonella sp in bulk and packaged meatballs sold at PD Pasar Surya in the East Surabaya Region and to determine the relationship between the hygiene and sanitation of traders on the level of bacterial contamination, Coliform contamination, Escherichia coli and Salmonella sp in bulk and packaged meatballs. This research is a cross sectional study and the sample was taken by purposive sampling method. The relationship between hygiene and sanitation of traders with microbiological quality of bulk meatballs and packaged meatballs using Chi Square. The results showed that the level of total bacterial contamination was higher in bulk meatballs (66.6%) compared to packaged meatballs (40%), Total Coliform bulk meatballs were 60% higher than packaged meatballs (40%), Escherichia coli meatballs Bulk meat (40%) is higher than packaged meatballs (20%), Salmonella sp in bulk meatballs (33.3%) is higher than packaged meatballs (40%). There is a significant relationship between the hygiene and sanitation of traders and the level of bacterial contamination, Coliform, Escherichia coli and Salmonella sp.